Photochemical smog modelling in Prague. (1st January 2001) - Bednar, J.; Brechler, J.; Halenka, T.
A model for simulation and evaluation of summer episodes of anthropogenic surface ozone (summer smog episodes) is presented in this paper. This model has been used for air-pollution studies in the region of Prague (central part of Bohemia, the Czech Republic). It is based on so-called "puff model" technology and the Lagrangian method of trajectory construction in the boundary layer of the atmosphere is applied. Processes of turbulent dispersion of puffs, photochemical and other chemical transformations and deposition of compounds on the Earth"s surface are also taken into account. A brief informative presentation of model results is included.